Edukasi Hipertensi dan Dampaknya pada Alokasi Biaya Kesehatan Rumah Tangga di Puskesmas Simpang Kawat Kota Jambi - Adila Solida; Evy Wisudariani; Fajrina Hidayati (Lembaga Pengembangan Kinerja Dosen, 2025)
The prevalence of hypertension in Jambi City has continued to increase over the past five years, including in the Simpang Kawat Community Health Center (Puskesmas Simpang Kawat). Meanwhile, the cost of hypertension care and treatment for the community is relatively high, especially if complications arise and are not covered by insurance, which can lead to catastrophic expenses that weaken households' economic conditions. This community service activity aims to provide education and outreach regarding hypertension and its impact on healthcare costs. Thirty people with hypertension in the Simpang Kawat Community Health Center (Puskesmas Simpang Kawat) participated in the activity. The core activities included providing information about hypertension and its consequences on healthcare costs, anti-hypertension exercises, outreach regarding the risk of catastrophic expenses, and explanations of various government support programs. The results showed that 80% of participants experienced a significant increase in knowledge, and there was a difference in knowledge levels between before and after the implementation of the Community Health Center (PPM) (p=0.000). The government and the Community Health Center are recommended to strengthen campaign efforts to encourage the community to adopt a healthy lifestyle and actively participate in health programs that can help reduce healthcare costs and avoid catastrophic expenses